Demonologie in die Nuwe-Testamentiese tydvak - Aarde, Andries van (Hervormde teologiese studies, 1986)
Demonology in New Testament times Modem demonology has become a cult just as it had been in mediaeval times. But there is a difference. Then people opposed the Devil; now people believe in the Devil. This paper argues that modem demonology is an escapism of reality and in direct contrast to the New Testament's message. The thesis is debated against the background of a discussion of demonology in New Testament times. In this discussion it is indicated how the face of evil has changed from Old Testament times up to the New Testament period. Evil has become an extraterrestrial figure, symbol and power. As the personification of the prince of evil, the Devil is inter alia identified with the mythological serpent in a lost paradise and is defeated at the realization of God's messianic kingdom in Jesus Christ, the prince of light. The New Testament proclaims that salvation means that man determines to exist as man of God before evil made man his slave.